Effect of clay mixing, irrigation and sulphur levels on soil fertility and productivity of mustard (Brassica juncea L.) - KUMAWAT, ARVIND; PAREEK, B. L.; PAREEK, N. K. (Journal of Soil and Water Conservation, 2021)
A field experiment on effect of clay mixing, irrigation and sulphur levels on soil fertility and productivity of mustard (Brassica- juncea L.) was conducted at farmers field, Jobner (Rajasthan) during Rabi seasons 2016-17 and 2017-18. The experiment consisted of 36 treatment combinations of 3 levels of clay mixing (0, 1 and 2 %), 3 levels of irrigation [1 irrigation at flowering stage, 2 irrigations at flowering and pod filling stages and 3 irrigations at branching, flowering and pod filling stages] as main plot treatments and 4 levels of sulphur (0, 30, 60 and 90 kg S/ha through gypsum) as sub plot treatments was laid out in split plot design with three replications. The results indicated that application of clay @ 2 per cent gave significantly higher yield attributes and yield and field water use efficiency in pooled mean over control and clay @ 1 per cent. The results further indicate that application of 3 irrigations resulted in significantly higher yield attributes and yield and field water use efficiency but remained at par with the application of 2 irrigations in siliqua per plant, seed and stover yield in pooled mean over the control. The application of sulphur @ 60 kg/ha gave significantly higher the yield attributes and yield in pooled mean basis over rest of treatments.